2017
DOI: 10.1007/s13592-016-0485-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of the antimicrobial activity of European propolis against Paenibacillus larvae

Abstract: -Typical European propolis is an antibiotic substance derived from the resin of poplar, birch, and aspen buds. Here, we tested the ability of propolis originating from the resins of these plants to inhibit the in vitro growth of Paenibacillus larvae , the organism that causes American foulbrood, a fatal honeybee larval disease. The study involved GC-MS analysis of extracts from nine samples of propolis gathered from the temperate climate zone of Europe. The extracts showed noticeable differences in the content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The isolates KB25, KB35, KB41, and KB55 used in this study were previously classified as P. larvae (Isidorov et al 2017) based on the colony shape (round, slightly whitish), lack of catalase, formation of spiral forms in the Plagemann test, and the 16S RNA sequences (Neuendorf et al 2004;Plagemann 1985). In this study, we determined that all of them belong to the ERIC I genotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The isolates KB25, KB35, KB41, and KB55 used in this study were previously classified as P. larvae (Isidorov et al 2017) based on the colony shape (round, slightly whitish), lack of catalase, formation of spiral forms in the Plagemann test, and the 16S RNA sequences (Neuendorf et al 2004;Plagemann 1985). In this study, we determined that all of them belong to the ERIC I genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Substantially, more active against the pathogen is propolis (Antúnez et al 2008;Bastos et al 2008;Bilikova et al 2013;Chen et al 2018;Isidorov et al 2016Isidorov et al , 2017Mihai et al 2012;Wilson et al 2015;Simone-Finstrom et al 2017). Extracts of this natural antimicrobial bee product demonstrated lower (as a rule, an order of magnitude) MIC values in tests with P. larvae than essential oils.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Macelignan and corosolic acid, the latter extracted from the banaba ( Lagerstroemia speciosa ) leaf, showed strong in vitro antibacterial activity against both P. larvae and M. plutonius [ 289 ]. Several studies are showing the in vitro ability of propolis extracts, from different botanical origins, or their constituents, to inhibit the growth of P. larvae [ 245 , 284 , 291 , 292 , 293 ]. Borba and Spivak [ 294 ], using colonies with and without a propolis envelope, demonstrated that the presence of the envelope provides an antimicrobial layer around the colony that protects the brood from P. larvae infection, resulting in a lower colony-level infection load.…”
Section: Antimicrobial Activity Of Labmentioning
confidence: 99%
“…29 The increasing use of this natural substance of diversified composition and therefore varying biological activities in the pharmaceutical, cosmetic, and food industries is generating particular interest in scientific research, especially when it comes to defining its chemical composition. Most studies have been carried out on samples from Europe 19,[30][31][32][33] and Latin America, more specifically Brazil, 20,23,[34][35][36] while few studies were conducted in Africa. [37][38][39][40][41] Information on Beninese and Congolese 42 propolis remains scarce.…”
mentioning
confidence: 99%